2015
DOI: 10.1016/j.erss.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the technological fix to climate change – Lay sense-making of geoengineering in Sweden

Abstract: This paper explores how Swedish laypeople make sense of emerging ideas of the large-scale deliberate technical manipulation of the global climate, known as geoengineering (GE). The paper is based on semi-structured focus group interviews with open-ended questions, allowing participants to express their spontaneous thoughts about GE. Although the focus group participants expressed great concern about climate change, GE was largely met with a sceptical, negative response. Participants perceived GE to: have negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…In a survey study, most respondents were against SAI being used as a way of continuing with carbon-intensive lifestyles (Mercer et al 2011). Furthermore, in two focus groups participants were in favour of increasing mitigation efforts once they had learned about SAI (Shepherd 2009, Wibeck et al 2015. These findings indicate no decrease in the perceived importance of mitigation as a result of knowledge about SAI and accordingly question the validity of the risk-compensation argument.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In a survey study, most respondents were against SAI being used as a way of continuing with carbon-intensive lifestyles (Mercer et al 2011). Furthermore, in two focus groups participants were in favour of increasing mitigation efforts once they had learned about SAI (Shepherd 2009, Wibeck et al 2015. These findings indicate no decrease in the perceived importance of mitigation as a result of knowledge about SAI and accordingly question the validity of the risk-compensation argument.…”
Section: Theorymentioning
confidence: 99%
“…Concern that mitigation efforts might decrease once stratospheric aerosol injection (SAI) was discussed as an option in the fight against climate change is strong both in scientific debate (Schneider 2001, Lawrence andCrutzen 2013) and among lay persons (Ipsos MORI 2010, Mercer et al 2011, Corner and Pidgeon 2014, Merk et al 2015, Wibeck et al 2015, Winickoff et al 2015. In scientific debate, this concern is referred to as 'risk compensation', 'moral hazard' or 'mitigation obstruction' (Betz and Cacean 2012, Keith 2013, Morrow 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous qualitative research (e.g., Corner et al 2013;Wibeck et al 2015) illustrated how lay people draw on various cultural narratives and linguistic strategies to make sense of climate engineering. While these studies were conducted in the global North, this paper expands the geographical and cultural scope and the empirical basis of the previous research into lay sensemaking about climate engineering.…”
Section: Introductionmentioning
confidence: 99%
“…However, CDR technologies, which are seen as more expensive and a more benign technologies, may in fact be more likely to cause moral hazard. For SAI, focus group studies (Shepherd, 2009;Wibeck, Hansson, & Anshelm, 2015) and a revealed-preference experiment (Merk, Pönitzsch, & Rehdanz, 2016) find that after learning about SAI, laypersons advocate increasing mitigation or buy more voluntary carbon offsets. Information about SAI also increases the perceived seriousness of climate change (Kahan, Jenkins-Smith, Tarantola, Silva, & Braman, 2015).…”
Section: Introductionmentioning
confidence: 99%